The dimensionality of consumer decision making styles : comparison between U.S. and Malaysian young consumers - Ang, Wooi Kok (2000)
A consumer decision-making style is defined as a mental orientation characterizing a consumer's approach to making consumer choices. All consumers are thought to approach the market with eight mental characteristics of consumer decision-making style: (1) Perfectionism or high-quality consciousness; (2) Brand consciousness; (3) Novelty-fashion consciousness; (4) Recreational, hedonistic shopping consciousness; (5) Price and "value for money" consciousness; (6) Impulsiveness; (7) Confusion from over choice of brands, stores, and consumer information; and (8) Habitual, brand-loyal orientation toward consumption. The purpose of this study is to identify the dimensionality of consumer decision-making styles of young consumers in Malaysia and to find if these styles are similar to those of U.S. young consumers. Most studies that have developed and validated models and instruments in consumer affairs research have used U.S. samples. However, companies and marketers cannot be based on research and survey conducted in U.S. to segment consumers in other countries. Such studies may be inapplicable. Thus, in this research, a questionnaire based on previous research in the U.S. was used to collect the data. Questionnaires were distributed to 250 university students at Universiti Putra Malaysia during December 2000. Of 212 returned questionnaires, 38 had incomplete information and were deemed invalid for this research. Data are factor analyzed and alpha coefficients are computed for scale reliability. The factor analysis explained 58 percent of the variance in the correlation matrix; a very reasonable proportion and all eigenvalues exceeded 1.0. Finding indicates that all the eight dimensions of consumers decision-making style were confirmed in Malaysia data. Decision-making styles of young consumers in Malaysia were classified, and several similarities and a few differences in decision-making styles were identified between Malaysia and U.S. consumers. The most important finding is that there is an indication of the generality of several consumer decision-making styles of young U.S. and Malaysia consumers. This study concludes with a discussion of these similarities and differences of consumer decision-making styles between young U.S. and Malaysia consumers.